Pengaruh Iklim Organisasi dan Budaya Organisasi terhadap Produktivitas Karyawan PT. Sri Muntari Lawe Sikap Aceh Tenggara - Hayati S, Munai; Utama, Indra (Medan Resource Center, 2023)
This article aims to analyze the effect of organizational climate and organizational culture on the productivity of PT. Sri Muntari Lawe Attitudes of Southeast Aceh. The method used in this research is quantitative. This research was conducted at pt. Sri Muntari lawe Attitudes of Southeast Aceh. The research method used in this study is the method of observation, documentation and questionnaires using a Likert scale. The sampling technique used saturated sampling which totaled 30 people. The analytical method used was multiple linear regression method using the SPSS program. The results of the study by partial test show that the organizational climate t count is 2.383> 2.052, so it can be concluded that the organizational climate variable has a positive and significant effect on the productivity of employees of PT. Sri Muntari Lawe Attitudes of Southeast Aceh. Organizational culture has a t count of 7.414 > 2.052 so it can be concluded that organizational culture variables have a positive and significant effect on employee productivity at PT. Sri Muntari Lawe Attitudes of Southeast Aceh. Based on the calculated F test of 28.200> 3.35, so that together organizational climate and organizational culture have a positive and significant effect on employee productivity. The results of the analysis of the coefficient of determination (R2) show that organizational climate and organizational culture have an influence on employee productivity, a value of 67.6% is affected, while the remaining 32.4% is influenced by other variables not examined in this study.